Pengaruh Work-Life Balance Terhadap Kinerja Karyawan Dengan Stres Kerja Dan Kepuasan Kerja Sebagai Variabel Intervening - Farhan Rafsanjani; Idayanti Nursyamsi; Maat Pono (Hasanuddin Journal of Business Strategy, 2019)
Employee satisfaction with organizational policies causes greater organizational productivity as a result of employee performance. This study aims to analyze the effect of work-life balance, job stress and job satisfaction on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk Makassar Panakkukang Branch. This study uses a saturated sampling technique, used a sample of 62 respondents employees of Makassar Panakkukang Branch Office. This writing data is obtained from questionnaires (primary), literature studies and direct interviews with related parties according to the purpose of writing. The analysis technique uses PLS data analysis consisting of structural models, measurement models, and Sobel models. The writing results show that work-life balance has a significant and negative effect on employee work stress, work-life balance also has a positive and significant effect on employee job satisfaction, while work-life balance does not directly influence employee performance, work stress has a negative and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, work-life balance through work stress has a positive and significant effect on employee performance and work-life balance through job satisfaction has a positive and significant effect on employee performance